Synthesis of rigidified flavin–guanidinium ion conjugates and investigation of their photocatalytic properties - Schmaderer, Harald; Bhuyan, Mouchumi; König, Burkhard (Beilstein Journal of Organic Chemistry, 2009)
Flavin chromophores can mediate redox reactions upon irradiation by blue light. In an attempt to increase their catalytic efficacy, flavin derivatives bearing a guanidinium ion as oxoanion binding site were prepared. Chromophore and substrate binding site are linked by a rigid Kemp’s acid structure. The molecular structure of the new flavins was confirmed by an X-ray structure analysis and their photocatalytic activity was investigated in benzyl ester cleavage, nitroarene reduction and a Diels–Alder reaction. The modified flavins photocatalyze the reactions, but the introduced substrate binding site does not enhance their performance.
Keywords: flavin; guanidine; Kemp’s acid; photocatalysis; template